The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.21203/rs.3.rs-971096/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stakeholders’ Perspectives on the Implementation of Maternity Waiting Homes in Rural Ethiopia: A Qualitative Study

Abstract: Background The rural community in Ethiopia is scattered over a wide geographic area, some regions with difficult mountains, making access to healthcare facilities a great challenge. To overcome geographical barriers and improve access to skilled childbirth care, maternity waiting homes (MWHs), shelters built nearby health facilities, where pregnant women are lodged until labour begins, were introduced decades ago. This study identifies the demand and supply-side determinants of access to MWH services in rural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…In our study, health workers were source of information about MWH. In support of this, other studies stated health workers to be sources of information about MWH [ 8 , 25 ]. This indicates that health workers can be a potential source of information about maternal health services including MWH.…”
Section: Discussionmentioning
confidence: 76%
“…In our study, health workers were source of information about MWH. In support of this, other studies stated health workers to be sources of information about MWH [ 8 , 25 ]. This indicates that health workers can be a potential source of information about maternal health services including MWH.…”
Section: Discussionmentioning
confidence: 76%
“…However, MWH use was found to be low in Ethiopia [ 6 ], and women's access to it mainly depended on male partner (husbands') decisions [ 7 , 8 ]. Male partners have important responsibilities, such as making decisions and setting up funds for the mother and infant to utilize during MWH stays, as well as for food, cleaning supplies, and transportation [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that integrating male partners in women's health could enhance the use of MWHs and other maternal health services. Lack of knowledge of MWHs, opinions of the services as being of low quality, poor providers interactions with MWH users, staffing deficit, and home tasks were among the obstacles to MWHs [ 8 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ethiopia has implemented MWHs over the last several decades 7 . However, the MWH utilization is low in Ethiopia 8 and women’s use of MWHs largely depends on male partners decisions 9 , 10 . Literatures revealed that male partners’ made the decision to stay at MWHs and some women did not use MWHs because their husbands refused to allow them to stay at MWHs 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the MWH utilization is low in Ethiopia 8 and women’s use of MWHs largely depends on male partners decisions 9 , 10 . Literatures revealed that male partners’ made the decision to stay at MWHs and some women did not use MWHs because their husbands refused to allow them to stay at MWHs 10 , 11 . In addition, an observational study from northern Ethiopia showed that half of the male partners did not involve in MWHs 12 .…”
Section: Introductionmentioning
confidence: 99%